2016
DOI: 10.1016/j.canlet.2015.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain containing protein represses the Ras/Raf/MEK/ERK pathway to attenuate human hepatoma cell proliferation during HCV infection

Abstract: Hepatitis C virus (HCV) infection facilitates the development of hepatocellular carcinoma (HCC). Activation of Ras/Raf/MEK/ERK pathway is found in more than 30% human cancers. Here, we revealed a novel mechanism underlying the regulation of hepatoma cell proliferation mediated by HCV. On one hand, hepatoma cell proliferation is facilitated by HCV infection through a positive feedback regulatory cycle. HCV promotes hepatoma cell proliferation by activating the Ras/Raf/MEK/ERK pathway, which in turn facilitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…ERK1/2 is strongly activated by HG stimulation [35]. A recent study showed that activation of Ras/Raf/MEK/ERK pathway increased BRD7 expression in hepatoma cell during HCV infection [36]. Then, we investigated whether HG-induced activation of ERK1/2 facilitated the expression of BRD7 in H9c2 cardiomyoblasts.…”
Section: Discussionmentioning
confidence: 98%
“…ERK1/2 is strongly activated by HG stimulation [35]. A recent study showed that activation of Ras/Raf/MEK/ERK pathway increased BRD7 expression in hepatoma cell during HCV infection [36]. Then, we investigated whether HG-induced activation of ERK1/2 facilitated the expression of BRD7 in H9c2 cardiomyoblasts.…”
Section: Discussionmentioning
confidence: 98%
“…The ERK1/2 cell signaling pathway is a well known cell proliferation signal as is the PI3K/AKT cell signaling pathway. In various tumors, down‐regulation of ERK1/2 MAPK signaling inhibits proliferation and migration of cells and also induces apoptosis of cells including prostate cancer cells [Park et al, ; Zhang et al, ]. Inhibition of P38 MAPK by TNF‐α specifically induces apoptosis of prostate cancer cells [Gil‐Araujo et al, ]; however, the level and subtype of JNK inducing apoptosis is very controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of BRD7, in contrast, leads to differential expression of 12 genes that are involved in the MAPK/ERK and Rb/E2F signaling cascades [ 27 ]: these include the downregulation of MEK1, GRB2, and E2F3, and upregulation of CDC42. This suggests that BRD7 is involved in cell proliferation [ 28 ] and that the suppression of cell cycle progression by BRD7 occurs via the transcriptional regulation of key proteins involved in the cell cycle. Further studies in HNE1 NPC cells as well as COS7 cells show that BRD7 is localized primarily in the nucleus, and contains a nuclear localization signal (NLS) from amino acid residues 65 to 96 [ 81 ].…”
Section: Brd7 In Cancermentioning
confidence: 99%